2014
DOI: 10.1038/bmt.2013.224
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of HLA-haploidentical hematopoietic SCT without in vitro T-cell depletion for adult severe aplastic anemia after modified conditioning and supportive therapy

Abstract: HLA-haploidentical hematopoietic SCT (HSCT) is an option for severe aplastic anemia (SAA) patients. Here, we evaluated the outcomes of 26 adult-SAA patients who received HLA-haploidentical HSCT in five transplant centers in southwestern China. Most of the patients in this study failed prior therapy and were transfused heavily before the transplantation. The patients received fludarabine þ cyclophosphamide þ antithymocyte globulin as conditioning regimens and then unmanipulated peripheral blood plus marrow tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 31 publications
4
49
2
Order By: Relevance
“…In these small series, rejection has been between 6% and 25%, acute GVHD between 12% and 30%, chronic GVHD between 20% and 40%, and overall survival between 62.5% and 84.6% [4244]. In the largest and most recently published cohort from China [37], 101 patients prospectively received haploidentical BMT from June 2012 through October 2015.…”
Section: Discussionmentioning
confidence: 99%
“…In these small series, rejection has been between 6% and 25%, acute GVHD between 12% and 30%, chronic GVHD between 20% and 40%, and overall survival between 62.5% and 84.6% [4244]. In the largest and most recently published cohort from China [37], 101 patients prospectively received haploidentical BMT from June 2012 through October 2015.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the kinetics of IR in patients with SAA after haplo-SCT have only been described for a relatively small number of cases. 13,14,[26][27][28] Koh et al 26 depicted CD3 + , CD4 + and CD56 + cell reconstitution after haplo-SCT using CD3 or CD3/CD19 depletion conditioning in four SAA patients. Their data showed that three of the four patients achieved CD3 + cell counts of 4400 cells/μL and CD4 + cell counts of 4150 cells/μL on day 180.…”
Section: Discussionmentioning
confidence: 99%
“…MMF (7.5 mg/kg twice per day) was started on day þ1 and was discontinued on day þ90. Acute GVHD (aGVHD) and chronic GVHD (cGVHD) were treated as previously described by Gao L. et al [16,17].…”
Section: Graft-versus-host Disease Prophylaxis and Managementmentioning
confidence: 99%